OPTN/SRTR 2019 Annual Data Report: Heart. Issue 2 (17th February 2021) - Colvin, M.; Smith, J. M.; Ahn, Y.; Skeans, M. A.; Messick, E.; Goff, R.; Bradbrook, K; Foutz, J.; Israni, A. K.; Snyder, J. J.; Kasiske, B. L.
Abstract: The new adult heart allocation policy was approved in 2016 and implemented in October 2018. This year's Annual Data Report provides early insight into the effects of this policy. In 2019, new listings continued to increase, with 4086 new candidates. Also in 2019, 3597 heart transplants were performed, an increase of 157 (4.6%) from 2018; 509 transplants occurred in children and 3088 in adults. Short‐ and long‐term posttransplant mortality rates improved. Overall, Mortality rates for adult recipients were 6.4% at 6 months and 7.9% at 1 year for transplants in 2018, 14.4% at 3 years for transplants in 2016, and 20.1% at 5 years for transplants in 2014. Mortality rates for pediatric recipients were 6.3% at 6 months and 8.2% at 1 year for transplants in 2018, 10.3% at 3 years for transplants in 2016, and 17.8% at 5 years for transplants in 2014.